CdS modified TiO2 films showing multicolor switching and enhanced optical contrast. Issue 38 (20th September 2016) - Luo, Gui; Shen, Kui; Zheng, Jianming; Xu, Chunye
Abstract : The electrochromic performance of a TiO2 /CdS film was first systematically studied. The TiO2 /CdS film exhibits multistage color switching under different potentials, improved optical contrast and half shortened coloration time. This work gains insight into inorganic EC materials from metal oxides to metal-chalcogenides. Abstract : In this work, we first studied the effects of CdS quantum dot modification on the electrochromic properties of TiO2 films in a Li ion containing organic electrolyte. Driven by an external potential, the CdS modified TiO2 (TiO2 /CdS) film achieves reversible coloration and discoloration. In particular, the TiO2 /CdS film exhibits multistage color switching from yellow (original state), to green (−1.5 V), to black (−2 V) in the coloration process, then to brown (−0.6 V) in the discoloration process. Besides, an improved optical contrast window of about 79.7% at 624 nm, an enhanced coloration efficiency of 70.8% and a half shortened coloration time of 12.7 s are achieved for the TiO2 /CdS film, when compared with those of a pure TiO2 film. This work not only presents a novel electrochromic material with enhanced electrochromic properties, but also brings us a new insight into exploring the electrochromic functions of metal-chalcogenides.